Educational History Game Based on Hero Struggle Stories to Strengthen the Patriotic Character of Elementary School Students - Yulia Siska; Andri Wicaksono; Ambyah Harjanto; Mareyke Jessy Tanod; Irfan Bayu Saputra (Vidya Karya, 2026)
Local history learning in elementary schools plays an important role in developing students’ national identity and patriotic character. However, history instruction is often delivered through memorization-based approaches with limited interactive media, resulting in low engagement and weak value internalization. This study aimed to develop and evaluate a narrative-based educational history game incorporating local hero struggle stories to strengthen the patriotic character of elementary school students. The research employed a research and development method using the ADDIE model. Participants consisted of three expert validators, one teacher, and 25 fifth-grade students in an elementary school in Bandar Lampung, Indonesia. Data were collected through validation questionnaires, user responses, and pretest–posttest instruments. Results showed the game achieved very high feasibility (97.5%), was very practical for teachers (92.5%), and highly attractive for students (95%). Effectiveness testing indicated significant improvement in students’ historical understanding and patriotic character, supported by moderate N-gain results (0.66). The findings contribute practically by providing an interactive learning medium for elementary history instruction and theoretically by supporting the integration of narrative-based game learning for character education.